Batman [videorecording (Blu-Ray)] - Elfman, Danny; Prince (Distributed by Warner Home Video, 2010)
After a young boy witnesses the murder of his parents on the streets of Gotham City, he grows up to become a mysterious figure in the eyes of Gotham City's citizens, known as Batman. He takes crime-fighting within the city into his own hands. Jack Napier becomes horribly disfigured after a firefight in a chemical factory, and becomes known as the Joker. Now, the Joker is out for revenge on his former employer.